Obstetric Delivery Practices and Malpractice Claims: Is There a Correlation? [26R]. (May 2017) - Baja, Angela; Miller, Lauren; Mills, Emily; Clarke, Bayley; Zarlengo, Gerald
Abstract : INTRODUCTION: This study assesses the correlation in trends between obstetric delivery practices and liability claims over 30 years. METHODS: A retrospective chart review was performed at a single Colorado hospital, averaging 4, 690 deliveries per year, from alternating years between 1978 and 2012. The number of cesarean sections (CS), operative vaginal deliveries (OVD) and vaginal lacerations (3rd and 4th degree) were recorded. A database of obstetrics liability claims, provided by COPIC Insurance, was tabulated and correlated with delivery data. All liability data was occurrence based and aggregated per year. Analysis was performed with Pearson correlation coefficients. RESULTS: The CS rate for singletons increased from 13% to 25% from 1978 to 2012. OVDs decreased from 14% to 2.5%. Lacerations decreased from 10.2% to 1.5%. The number of obstetric claims increased steadily until 2006 and then decreased. There was a significant positive correlation between CS rates and obstetrics claims (P =.006). No significant correlation was found between OVD rates and liability claims (P =.073) or lacerations and liability claims (P = .052). CONCLUSION: A positive correlation between CS rates and liability claims was noted, while no correlation in OVD or laceration rates to liability claims was found. Together, these trends suggest that abandonment of OVD has not been protective from a liability perspective. The decreasing rates of CS and malpractice claims starting in 2006 are likely explained by Colorado's medical tort reform in 2003. Undoubtedly fear of malpractice affects obstetricians' management, however abandoning OVD in favor of CS has not proven to be a protective solution.